2016
DOI: 10.4194/1303-2712-v16_4_01
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Fish welfare at slaughter is an area of considerable scientific and commercial importance during the last decade. The aim of this study was to evaluate the effect of three stunning procedures on stress and meat quality of common carp. The experimental fish were separated in three groups and stunned by percussion (Group PS), electricity (Group ES) or asphyxia (Group AS), followed by decapitation. Blood cortisol and glucose concentrations were measured as stress indicators, whereas drip loss was used as meat qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…As it was discussed by Daskalova et al (2016b), the impairment of water-holding capacity is of great importance, as it is substantial in commercial processing practice. Water-holding capacity is an essential fresh meat property, because it affects the yield and quality of the end product.…”
Section: Stress-related Changes In Post-mortem Muscle Metabolism and mentioning
confidence: 99%
“…As it was discussed by Daskalova et al (2016b), the impairment of water-holding capacity is of great importance, as it is substantial in commercial processing practice. Water-holding capacity is an essential fresh meat property, because it affects the yield and quality of the end product.…”
Section: Stress-related Changes In Post-mortem Muscle Metabolism and mentioning
confidence: 99%
“…One of the most critical steps in fish welfare occurs in the slaughter phase, with hormonal, biochemical, osmoregulatory and energetic alterations. These changes can affect the meat quality, with changes in colour and texture of the fillets, protein degradation, and lipid and metabolic oxidation (Daskalova et al,2016; Zampacavallo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…
One of the most critical steps in fish welfare occurs in the slaughter phase, with hormonal, biochemical, osmoregulatory and energetic alterations. These changes can affect the meat quality, with changes in colour and texture of the fillets, protein degradation, and lipid and metabolic oxidation (Daskalova et al,2016;Zampacavallo et al, 2015).Various methods for stunning and killing fish have been studied, such as electrical current application, cranial percussion, hypothermia, asphyxiation, CO 2 narcosis, anaesthesia, and spiking. Among these methods, stunning by hypothermia has been one of the most used by the fish industry (Zampacavallo et al, 2015; Oliveira Filho, Oliveira, et al, 2015a; Oliveira Filho, 2015b).
…”
mentioning
confidence: 99%
“…The lack of a clear stress response for cortisol in fish has been previously reported. The common carp (Cyprinus carpio L.) stunned by percussion, showed the lowest average glucose concentration in the blood plasma (87 ng/mL; 16-665) (median: Q1-Q3) as compared to fish stunned by electricity (800; 14-800) and asphyxia (800; 800-800) (Daskalova et al, 2016). Daskalova et al (2016) reported serious difficulties in statistical processing and the inability to calculate averages due to the cortisol values, and the authors attributed such differences to individual neuroendocrine and behavioural differences.…”
Section: Discussionmentioning
confidence: 99%
“…The common carp (Cyprinus carpio L.) stunned by percussion, showed the lowest average glucose concentration in the blood plasma (87 ng/mL; 16-665) (median: Q1-Q3) as compared to fish stunned by electricity (800; 14-800) and asphyxia (800; 800-800) (Daskalova et al, 2016). Daskalova et al (2016) reported serious difficulties in statistical processing and the inability to calculate averages due to the cortisol values, and the authors attributed such differences to individual neuroendocrine and behavioural differences. In several cases a high biological variability in cortisol values was reported amongst individuals submitted to the same experimental conditions, suggesting that cortisol measurements should be complemented by other metabolic indicators to validate its results (Magalhães et al, 2018).…”
Section: Discussionmentioning
confidence: 99%